PENGARUH EDUKASI SELF-MANAGEMENT TERHADAP PENINGKATAN PERILAKU PENCEGAHAN PENYAKIT JANTUNG PADA PASIEN HIPERTENSI DI DESA BANGUN REJO TAHUN 2026 - Adelina Sembiring; Lisdayanti Simanjuntak; Petra Diansari Zega; Lisbet Gurning; Sri Mulati Nendah Agreta; Srilina Br Pinem; Nur Azizah; Angel Shesapatrisia Girsang; Anisa Br Munte (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Background: Hypertension is one of the major risk factors for cardiovascular disease and remains a leading cause of mortality worldwide. Effective hypertension control depends not only on pharmacological therapy but also on patients' ability to perform self-management, including medication adherence, adherence to a low-sodium diet, regular physical activity, stress management, smoking cessation, and routine blood pressure monitoring. The low level of heart disease preventive behaviors among patients with hypertension remains a significant public health challenge. Therefore, effective educational interventions are needed to enhance patients' self-management abilities and promote healthier behaviors. Objective: This study aimed to determine the effect of self-management education on improving heart disease preventive behaviors among patients with hypertension in Bangun Rejo Village in 2026. Methods: This study employed a pre-experimental design using a one-group pretest-posttest approach. The study population consisted of all patients with hypertension in Bangun Rejo Village. The sample was selected using purposive sampling based on predetermined inclusion and exclusion criteria. The intervention consisted of self-management education delivered through health education sessions, group discussions, demonstrations, and educational media throughout the study period. Data were collected using a validated and reliable questionnaire on heart disease preventive behaviors. Data analysis included univariate analysis to describe respondents' characteristics and bivariate analysis using the Wilcoxon Signed Rank Test (or the Paired t-test if the data were normally distributed), with a significance level of α = 0.05. Results: The findings demonstrated an increase in the mean score of heart disease preventive behaviors following the self-management education intervention. Statistical analysis indicated that self-management education had a significant effect on improving heart disease preventive behaviors among patients with hypertension (p 0.05). Conclusion: Self-management education is effective in improving heart disease preventive behaviors among patients with hypertension. This intervention can serve as a promotive and preventive strategy in community health services to enhance hypertension control and reduce the risk of cardiovascular disease.Keywords: Hypertension, Self-Management, Education, Preventive Behavior, Heart Disease